Perbedaan perilaku investasi antara pria dan wanita - putri, sofiyah amalun (Maliki Interdisciplinary Journal, 2026)
This research aims to thoroughly examine the differences in investment behavior between male and female infestors. Within the financial sector, decision-making characteristics are frequently influenced by various factors, one of which is gender distinction, as it tends to shape distinct minsets and attitudes. This study employs a quantitative descriptive method involving a number of respondents who are actively engaged in investment activities. The collected date were processed and analyzed to identify significant differences regarding risk tolerance levels, self confidence, and the strategies implemented. The findings reveal that there are noticeable differences in how men and women manage their investment assets. In general, male investors tend to be more risk tolerant and act more decisively, whereas female investors demonstrate a more cautious, analytical approach with a focus on long term planning. It is expected that these results will provide valuable insight for financial institutions and investor alike, assingting them in understanding market psychology and determining appropriate investment strategies.